Urgensi Pembentukan Hakim Komisaris dalam Pembaharuan Peradilan Pidana Indonesia Berdasar Nilai Keadilan Pancasila - Ghozali, Imam (Fakultas Syariah INSURI Ponorogo, 2022)
The criminal justice system, which must be interpreted as a criminal law enforcement system, has been narrowed to its constitutional meaning in Indonesia. Therefore, efforts are needed to maintain the nature of the system as a system of judicial power that must be independent in order to ensure the justice and material truth so that it becomes an ideal criminal justice system. The following description tries to explain the existence of the institution of commissioner judges as part of the renewal of criminal law (formil) which can be a safety valve in realizing the form of the criminal justice system in the future.